DETERMINATION OF OFFSHORE STRUCTURE LRFD ENVIRONMENTAL LOAD FACTOR IN MAKASSAR SEA USING RELIABILITY ANALYSIS - Fathurridho Hermanto, Mochammad
As the fourth most populous country in the world, Indonesia's need for energy is enormous. As the largest archipelagic country in the world, Indonesia also has enormous marine potential, including oil and natural gas. In order to obtain oil and natural gas, offshore platforms are required. Offshore platform must be strong and stable to withstand all working loads. The structure design of the offshore platform could refer to API RP-2A by two different methods, WSD or LRFD. The WSD method assumes that all load and structural strength variables have deterministic values. Meanwhile, the LRFD method takes into account the uncertainty factor on the load and structural strength variables. This consideration is manifested in the form of load factor and resistance factor. Therefore, the LRFD method is considered more suitable because in reality, the working load and the capacity of the structure are random. API RP-2A LRFD obtains the environmental load factor (????????) from environmental conditions in the waters of the Gulf of Mexico. The significant wave height in the Gulf of Mexico reaches 12.05 m (Korobkin and D'Sa, 2008) compared to the significant wave height in Makassar Sea which only reaches 3.73 m based on SEAFINE data. Due to these different approach, an environmental load factor that is more suitable for Indonesian waters is needed so that the structure design is more optimal. In this study, the base shear is analyzed to describe the strength of the structure in the form of collapase base shear (CBS) and the load in the form of a wave base shear (WBS). CBS is obtained through pushover analysis with yield strength randomness. WBS is obtained through inplace analysis with wave height randomness. This concept is applied to the structure of the Monopod and Braced Monopod types of offshore platforms located in Makassar Strait waters which have been optimized for the WSD and LRFD design methods. The reliability of the structure is analyzed based on the CBS and WBS values using the First Order Reliability Method (FORM) II. The results of the reliability analysis are in the form of a reliability index (????). With a reliability index target of 3.09, Monopod structure environmental load factor (????????) recommendation can’t be determined because the reliability index of LRFD 3.53 and WSD 3.54. The Braced Monopod structure meets the target reliability index with the reliability index of LRFD 4.99 and WSD 5.13. Based on these results, Monopod and Braced Monopod are recommended to use environmental load with return period less than 100 year to make the design more efficient based on 3.09 target reliability index..